COMMENTS ON THE REPORTED METHOD OF EMPLOYING GREATER MAGNIFICATION FOR THE OVA-DIAMETER STUDIES IN FISHES - Raja, B T Antony (Indian Journal of Fisheries, 2011)
Examining critically the use of high-power magnification for the ova-diametermeasurements asreportedinanearlier work, it has been pointed out that the method isnot an advaiice over the more conventional method where a low magnification is used.Besides being laborious, it does not ensure any accuracy in measurements and mayfurther give rise to misleading results